Contribution of Internal Control System towards Financial Performance: An Empirical Configuration for Future Strategies - Chaudhary, Manoj Kumar; Chaudhary, Rajesh Kumar (Patan Pragya, 2022)
Internal control system in an organization preventing the dishonest financial reporting is the need of present scenario especially in Nepalese financial institutions. Therefore, this study intends to present the contribution of internal control system towards financial performance in Nepalese commercial banks. To know the contribution of internal control system descriptive research design has been applied to assess the current practice of internal control system and its effect on financial performance in Nepalese commercial banks. In this 280 employees from top 7 commercial banks were selected based on their paid up capital as the sample for this study. The result depicts that internal control has significant relation with financial performance in commercial banks of Nepal. Therefore, this study concludes that internal control system mainly control environment and internal audit have the significant contribution to the financial performance while considering liquidity and profitability in Nepalese context. Hence, the result of the study will have significant contribution for the concern authorities to make their future strategies for the irresponsible financial reporting.